2004
DOI: 10.4028/www.scientific.net/msf.465-466.465
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Bonding Interface in Explosively-Welded Clads and Bonding Mechanism

Abstract: Microstructural aspects and bonding characteristics of the explosive welded Ti/Ti, Ti/steel and Ti/Ni clads were investigated mainly by TEM microscopy. It was found that the bonding interface was composed of layers of metastable phases such as amorphous phases, icosahedral quasicrystal and intermetallic compounds. These metastable phases are formed as a trace of melting followed by subsequent rapid solidification of thin layers of about 200 nm in thickness along the contact surface of both the component materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…[21][22][23][24][25][26][27][28][29] Explosive welding involves the initial melting and ejection of surface, followed by the formation of straight sections and vortices alternating along the wavy interface. Either crystalline phases or isocahedral/amorphous phases [30] can be found at the straight sections of bonding, and resolidified microstructures [31,32,33] attributable to additional adiabatic heating and melting are identified at the vortex cores. In contrast, the wakes in ultrasonic welds occur in the absence of any microstructural evidence of melting at micrometer scale.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29] Explosive welding involves the initial melting and ejection of surface, followed by the formation of straight sections and vortices alternating along the wavy interface. Either crystalline phases or isocahedral/amorphous phases [30] can be found at the straight sections of bonding, and resolidified microstructures [31,32,33] attributable to additional adiabatic heating and melting are identified at the vortex cores. In contrast, the wakes in ultrasonic welds occur in the absence of any microstructural evidence of melting at micrometer scale.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the deformation at a high strain rate, elevated pressure at the contact point, and short duration of the explosive welding process may result in unique and uncommon structures at the interface between welded materials. Nishida et al [13,14] and Chiba et al [15] observed the formation of amorphous and quasicrystalline phases in explosively welded Ni-Ti bimetals. In addition, they found amorphous structures in explosively welded Ti-steel bimetals.…”
Section: Introductionmentioning
confidence: 98%
“…Such a layer can only be observed using transmission electron microscopy (TEM). In general, it has been found that the thickness of the observed layer is in the range of 100–300 nm (Chiba et al, 2004; Song et al, 2011; Paul et al, 2014; Guoyin et al, 2017) or thicker (Gloc et al, 2016; Wachowski et al, 2017; Lazurenko et al, 2018), depending on the location of the extracted TEM lamella (Chu et al, 2019). This thin interlayer has an amorphous or fine crystalline structure (Chiba et al, 2004; Yang et al, 2006; Chu et al, 2017; Guoyin et al, 2017; Lazurenko et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In general, it has been found that the thickness of the observed layer is in the range of 100–300 nm (Chiba et al, 2004; Song et al, 2011; Paul et al, 2014; Guoyin et al, 2017) or thicker (Gloc et al, 2016; Wachowski et al, 2017; Lazurenko et al, 2018), depending on the location of the extracted TEM lamella (Chu et al, 2019). This thin interlayer has an amorphous or fine crystalline structure (Chiba et al, 2004; Yang et al, 2006; Chu et al, 2017; Guoyin et al, 2017; Lazurenko et al, 2018). There are, however, some works on explosively welded titanium/steel joint using TEM (Song et al, 2011; Guoyin et al, 2017; Wachowski et al, 2017), where some discrepancies have been found in the description of the microstructure of the interface zone.…”
Section: Introductionmentioning
confidence: 99%